Insect Pests of Fast Growing Tree Species-I. Preliminary Investigation on Poplar Stem and Root Borer, Apriona cinerea Chevrolat (Coleoptera : Lamiidae) in New Forest - Chatterjee, P. N.; Thapa, R. S. (Indian Forester, 1964)
A preliminary account of poplar stem and root borer, Apriona cinerea and its control measures are given.